Electrospun mesoporous zirconia ceramic fibers for catalyst supporting applications. Issue 1 (January 2018) - Yuan, Kangkang; Jin, Xiaotong; Yu, Zhichao; Gan, Xinzhu; Wang, Xinqiang; Zhang, Guanghui; Zhu, Luyi; Xu, Dong
Abstract: Mesoporous zirconia has been widely used as supporting materials, absorption materials, catalysts and high temperature insulating materials. While seldom has taken a consideration of the mesoporous fiber structure. In the present work, mesoporous zirconia ceramic fibers were fabricated by electrospinning method with CTAB as the template. The thermal decomposition and crystallization process of the mesoporous zirconia fibers were fully studied by TG/DSC, IR spectra and XRD. The highest surface area of the mesoporous zirconia fibers was about 120 m 2 /g. With mesoporous zirconia fibers as the supporting materials, tungstate supported on zirconia fibers catalyst showed that the specific activity of bromination of phenol red was 1.26 mmol h −1  g −1 . The results confirmed that zirconia fibers with the mesoporous structure would be a promising candidate as a supporting material.